Development Of Lectora Inspire Based Learning Media For Human Body Anatomy - Aref Vai; Slamet Slamet; Agus Prima Aspa; Muhammad Imam Rahmatullah; Fitri Agung Nanda (Jurnal MensSana, 2020)
The times that show the existence of learning innovations using online devices require learning innovations. The purpose of this research is to develop learning media for human body anatomy based on Lectora Inspire. The method used in research which is research and development (Research & Development). Lectora Inspire is an application that is used to develop instructional media products. In this study, the researchers analyzed that learning human body anatomy based on lectora inspire was still not widely used. Therefore, research on this learning media is quite urgent to do. Researchers provide a different point of view regarding lectora inspire-based learning media. In doing the validation, the researchers tested the material, media and learning validation by experts in their fields. Data were analyzed using quantitative descriptive analysis techniques that were expressed in the distribution of scores and a predetermined category rating scale. The sample used involved students who took part in the learning. Based on the results of the evaluation in the field of material received an average score of 4.19 and categorized as good. Evaluation in the media sector has an average score of 4.31 and is categorized as good, and students' responses in the small group average score of 4.26 are categorized as good. From the results of this study it can be concluded that the Lectora Inspire application is very effective in using learning media, especially human anatomy because it is supported by features that can facilitate the learning process